The Effect of Web-based Educational Games Toward Student Learning Outcomes on The Topic of The Immune System - Dwi Ratna Julianti; R. Ading Pramadi; Meti Maspupah; Muhammad Muttaqin; Epa Paujiah (Indonesian Journal of Mathematics and Natural Science Education, 2022)
The purpose of this study was to analyze the effect of using web-based educational games on student learning outcomes on the immune system topic. This study uses Quasi Experiment method with a non-equivalent control group design. Data analysis technique using normality test, homogeneity test, and hypothesis testing in the form of t-test. The results showed that web-based educational games affected student learning outcomes in immune system topics at SMAN 3 Purwakarta. This finding is proved by the acquisition of the results of the t-test with a significance level of 5%, the value of t-count > t-table = 2.43 > 2.01. The score of learning outcomes on immune system topic in the experimental class is greater than that of the control class, namely the experimental class gets an average score of 78 while the control class gets an average score of 69.4. Therefore, it can be concluded that the use of web-based educational games has a positive effect on improving student learning outcomes on immune system topic.